Mitochondrial BMI1 maintains bioenergetic homeostasis in cells. Issue 12 (9th September 2016) - Mustafi, Soumyajit Banerjee; Aznar, Nicolas; Dhar Dwivedi, Shailendra Kumar; Chakraborty, Prabir Kumar; Basak, Rumki; Mukherjee, Priyabrata; Ghosh, Pradipta; Bhattacharya, Resham
ABSTRACT: The polycomb complex proto‐oncogene BMI1 [B lymphoma Mo‐MLV insertion region 1 homolog (mouse)] is essential for self‐renewal ofnormal andcancer stemcells. BMI1‐nullmice showseveredefects ingrowth, development, and survival. Although BMI1 is known to exert its effect in the nucleus via repression of 2 potent cellcycle regulators that are encoded by the Ink4a/Arf locus, deletion of this locus only partially rescues BMI1‐null phenotypes, which is indicative of alternatemechanisms of action of BMI1. Here, we showthat an extranuclearpool of BMI1 localizes to inner mitochondrial membrane and directly regulates mitochondrial RNA (mtRNA) homeostasis andbioenergetics. Thesemitochondrial functions of BMI1 are independent of itspreviouslydescribednuclear functions because a nuclear localization‐defective mutant BMI1 rescued several bioenergetic defects that we observed in BMI1‐depleted cells, for example, mitochondrial respiration, cytochrome c oxidase activity, and ATP production. Mechanistically, BMI1 coprecipitated with polynucleotide phosphorylase, a ribonuclease that is responsible for decay of mtRNA transcripts. Loss of BMI1 enhanced ribonuclease activity of polynucleotide phosphorylase and reduced mtRNA stability. These findings not only establish a novel extranuclear role of BMI1 in the regulation of mitochondrial bioenergetics, but also provide new mechanistic insights into the role of this protooncogene instemcell differentiation, neuronal aging, and cancer.—Banerjee Mustafi, S., Aznar, N., Dwivedi, S. K. D., Chakraborty, P. K., Basak, R., Mukherjee, P., Ghosh, P., Bhattacharya, R. Mitochondrial BMI1 maintains bioenergetic homeostasis in cells. FASEB J. 30, 4042–4055 (2016). www.fasebj.org